PENGEMBANGAN MODEL ASESMEN LITERASI DAN SAINS BERBASIS STEM BERORIENTASI PISA UNTUK SISWA KELAS X SMK BINTANG PERSADA - Putu Dessy Fridayanthi (Widyadari, 2026)
The implementation of the Science, Technology, Engineering, and Mathematics (STEM) approach has become a primary focus of 21st-century educational reform due to its relevance to the needs of the workforce and the development of critical thinking competencies. However, the availability of STEM-based literacy and science assessment instruments that adhere to the Programme for International Student Assessment standards remains limited, particularly at the vocational high school (SMK) level. According to a report by the Organisation for Economic Co-operation and Development (2022), Indonesian students' literacy and science achievements remain below the international average, necessitating innovation in assessment development. This study aims to: (1) analyze the characteristics of STEM-based literacy and science assessment instruments according to PISA standards, and (2) develop a STEM-based assessment model for 10th-grade students. The study used a mixed methods approach with a sequential exploratory design through the stages of exploration, design, development, validation, and instrument testing. The results show that the developed assessment instrument is contextual, multidisciplinary, and based on higher-order thinking skills (HOTS). The resulting assessment model proved valid (Aiken's V = 0.87), reliable (Cronbach's Alpha = 0.82), and effective in improving students' literacy and science skills. The conclusion of this study indicates that PISA-oriented STEM-based assessments can be an innovative alternative for improving the quality of learning and competency of vocational high school students.